Jean-Louis Chermant (June 24, 1941 – August 11, 2024) - Wojnar, Leszek (Image Analysis and Stereology, 2024)
Jean-Louis Chermant was widely known within the scientific community focused on image analysis and stereology, especially in materials science applications. He served as Vice President for Europe (1984-1988) and President of the International Society of Stereology (1988-1991). His engaging personality, coupled with his vast scientific knowledge, made him an outstanding manager and even a visionary.